IMPLEMENTASI LOAD BALANCING PADA MIKROTIK MENGGUNAKAN ROUTING PROTOCOL OSPF DI STMIK PRADNYA PARAMITA MALANG - Rizky Ismuyanto, Putri Gusti; Arifin, Samsul (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2023)
Campus STMIK Pradnya Paramita Malang currently using proxy type RB 750GL with two line with the bandwidth specification limit 3 Mbps upload and download 4 Mbps. Mikrotik in the current campus using routing features. Because the routing feature depends on the network load, the length of the diagram, the type of service requested, traffic patterns, and if there are changes or additions to the resources, the routing table must also be changed manually so often uneven distribution of bandwidth and result in unbalanced traffic. From the analysis, we conducted this study on the implementation of load balancing proxy using the OSPF routing protocol in STMIK Pradnya Paramita to get the network load, the length of the diagram, traffic patterns, and a more equitable distribution of bandwidth and balance. With the implementation of load balancing on a proxy using the routing protocol OSPF routing can update automatically on a regular basis so that when things go wrong or damage to the network, OSPF can specify another path as a backup path.